Mildly Processed Natural Eggshell Membrane Alleviates Joint Pain Associated with Osteoarthritis of the Knee: A Randomized Double-Blind Placebo-Controlled Study - Kiers, Jeroen Lucas; Bult, Johannes Hendrikus Franciscus (Journal of medicinal food, 2021)
Poor joint health is a significant burden to society. Millions of people suffer from some form of joint-related disorder or disease, most often osteoarthritis (OA). It was hypothesized that chicken eggshell membrane (EM) is effective in the regeneration of cartilage and/or immunomodulation (oral tolerance), and as such relieves pain and stiffness in joints commonly affected in arthritis. We tested this hypothesis in a double-blind, placebo-controlled EM intervention study. Of 150 male and female volunteers, 40-75 years of age and diagnosed with knee OA, 75 were randomly assigned to the EM intervention group and 75 to the placebo group. During 12 weeks, subjects received a daily capsule containing either 300 mg of EM or a placebo. The main primary dependent variable consisted of self-reported pain ratings on a Numerical Rating Scale Pain (NRS-P) 6 weeks after study start. As secondary dependent variables served NRS-P scores collected after 12 weeks, and Knee injury and self-reported Osteoarthritis Outcome Scores (Knee injury and Osteoarthritis Outcome Scores [KOOS]). NRS-P scores decreased for both groups at approximately the same rate, but only EM relieved self-reported pain scores obtained with the KOOS questionnaire starting 1 week after initiation of treatment. This effect was significant for two of five KOOS category scores, that is, "Pain" and "Daily Life" functioning, aggregate pain, and functioning scores composed of complaint ratings for a wide variety of daily activities. These scores showed long-lasting improvement, and demonstrated that EM extract successfully reliefs knee OA pain and contributes to daily life functioning.